Diphenylmaleimide derivatives and their efficiency in off-on Hg2 fluorometric sensing - Wainiphithapong,C. (Maejo University, 2015)
Two novel fluoroionophores (Sensors 1 and 2) possessing one and two units of diphenylmaleimide fluorophore covalently bound to 2-[3-(2-aminoethylsulfanyl)propylsulfanyl] ethanamine were prepared for the selective detection of Hg2+ ions. The binding ability with Hg2+ was investigated by fluorescence spectroscopy. Sensor 1 exhibited highly sensitive and selective off-on fluorescence enhancement at 500 nm upon binding to Hg2+ and was shown to discriminate various competing metal ions, particularly Cu2+ and Pb2+, as well as Li+, Na+, Mg2+, Cd2+, K+, Al3+, Fe3+, Ca2+, Ba2+, Co2+, Mn2+ and Zn2+ with a detection limit of 6.72 × 10-7 M. On the other hand, Sensor 2 was found to be inferior fluoroionophore to Sensor 1 in terms of selectivity in the presence of competitive ions such as Mn2+ and Al3+. © 2012 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.